Musical instruments of Asia and the Pacific [videorecording] - Asia/Pacific Cultural Centre ([S.l.] ACCM, 1995)
Presents musical instruments from eighteen Asia/Pacific countries with scenes of playing each instrument and the process of manufacturing it. In this video, musical instruments are classified into three categories : string, wind and percussion.
VHS.
Keywords: Instrumental music -- Asia; Musical instruments, Asian; Musical instruments, Pacific